Global disease burden of conditions requiring emergency surgery. Issue 1 (25th November 2013) - Stewart, B.; Khanduri, P.; McCord, C.; Ohene‐Yeboah, M.; Uranues, S.; Vega Rivera, F.; Mock, C.
<x xml:space="preserve">Abstract</x> Background Surgical disease is inadequately addressed globally, and emergency conditions requiring surgery contribute substantially to the global disease burden. Methods This was a review of studies that contributed to define the population‐based health burden of emergency surgical conditions (excluding trauma and obstetrics) and the status of available capacity to address this burden. Further data were retrieved from the Global Burden of Disease Study 2010 and the University of Washington's Institute for Health Metrics and Evaluation online data. Results In the index year of 2010, there were 896 000 deaths, 20 million years of life lost and 25 million disability‐adjusted life‐years from 11 emergency general surgical conditions reported individually in the Global Burden of Disease Study. The most common cause of death was complicated peptic ulcer disease, followed by aortic aneurysm, bowel obstruction, biliary disease, mesenteric ischaemia, peripheral vascular disease, abscess and soft tissue infections, and appendicitis. The mortality rate was higher in high‐income countries (HICs) than in low‐ and middle‐income countries (LMICs) (24·3 versus 10·6 deaths per 100 000 inhabitants respectively), primarily owing to a higher rate of vascular disease in HICs. However, because of the much larger population, 70 per cent of deaths occurred in LMICs. Deaths from vascular disease rose from 15 to 25 per cent of surgical emergency‐related deaths in LMICs (from 1990 to 2010). Surgical capacity to address this burden is suboptimal in LMICs, with fewer than one operating theatre per 100 000 inhabitants in many LMICs, whereas some HICs have more than 14 per 100 000 inhabitants. Conclusion The global burden of surgical emergencies is described insufficiently. The bare estimates indicate a tremendous health burden. LMICs carry the majority of emergency conditions; in these countries the pattern of surgical disease is changing and capacity to deal with the problem is inadequate. The data presented in this study will be useful for both the surgical and public health communities to plan a more adequate response.